Sexual violence among female commuter line passengers in Jakarta - Toni, Ahmad; Maknunah, Jauharotul (Jurnal Sosiologi Dialektika, 2025)
This topic of this research is sexual violence that occurred on commuter line electric trains in the Jabodetabek area. This study aims to investigates the experiences of women victims of sexual violence on commuter line trains. Taking a social setting in the Jabodetabek area, namely the Jakarta-Tangerang City, Jakarta-Rangkasbitung Banten, Jakarta-Bekasi West Java and Jakarta-Bogor West Java routes, the researcher also explored the factors of victims not reporting the violence experienced and the conditions after experiencing violence. This study uses a case study method, with 149 commuter line KRL passengers as research subjects. The findings show that 24 passengers on the Jakarta-Tangerang City route, 1 in 6 passengers experienced sexual harassment and occurred in 2018, and 2023. Data from 41 female users of the KRL computer line on the Jakarta-Rangkasbitung Banten route, 1 in 4 women have experienced sexual harassment. Meanwhile, data from 38 female passengers who were interviewed on the Jakarta-Bekasi route in West Java showed that 1 in 5 passengers experienced sexual harassment while they were using the KRL commuter line. Data from 46 female passengers interviewed showed that 1 in 4 women had experienced sexual harassment on the Jakarta-Bogor West Java KRL route. The conclusion of this study shows that the process of silencing victims of sexual violence because the stigma of the victim is negative, the victim is placed in the position of the guilty party, unable to protect themselves, obliged to accept this behaviour, and must be silent to accept their weak nature.